The expected scenarios on the economic variables of developing countries after the Corona crisis - Omar, Dina Ahmed; Dames, Dr. Zakaria Hassan Hussein Abu (International Journal of Psychosocial Rehabilitation, 2020)
The world is living in these days a great health crisis that had clear effects, and not the same as its predecessors of similar crises and made an important difference on the level of international and economic policy, in various political, economic and social aspects and created great confusion in paralyzing the global movement entirely, and this paralysis still exists, so this study examines In highlighting the impact this crisis has on the political and economic fields of the world as a serious attempt to find a real and expected comparison of this crisis.